2012
DOI: 10.1073/pnas.1204580109
|View full text |Cite
|
Sign up to set email alerts
|

Supramodal numerosity selectivity of neurons in primate prefrontal and posterior parietal cortices

Abstract: Numerosity, the number of elements in a set, is a most abstract quantitative category. As such, it is independent of the sensory modality of its elements, i.e., supramodal. Because neuronal numerosity selectivity had never been compared directly across different sensory modalities, it remained elusive if and where single neurons encode numerosity irrespective of the items’ modality. Here, monkeys were trained to discriminate both the number of auditory sounds and visual items within the same session. While the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
172
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 169 publications
(189 citation statements)
references
References 45 publications
14
172
3
Order By: Relevance
“…Second, neuronal discharges of selective neurons proved to be relevant for the crows' correct performance; if the neurons did not properly encode their preferred numerosity, the crow was prone to make mistakes. Similar results have been reported repeatedly for numerosity-selective neurons in monkeys (10)(11)(12)(13)(14)(15)(16)(17)(18). Third, both the neuronal and the behavioral tuning functions were best described on a logarithmic number line, arguing for a nonlinearly compressed coding of numerical information.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Second, neuronal discharges of selective neurons proved to be relevant for the crows' correct performance; if the neurons did not properly encode their preferred numerosity, the crow was prone to make mistakes. Similar results have been reported repeatedly for numerosity-selective neurons in monkeys (10)(11)(12)(13)(14)(15)(16)(17)(18). Third, both the neuronal and the behavioral tuning functions were best described on a logarithmic number line, arguing for a nonlinearly compressed coding of numerical information.…”
Section: Discussionsupporting
confidence: 68%
“…Our behavioral and neuronal data show an impressive correspondence of neuronal mechanisms found in the avian brain with those reported earlier in the nonhuman and human primate brain: First, NCL neurons were tuned to individual preferred numerosities characteristic of a "labeled-line code," enabling an unequivocal representation of numerosity by a neuronal population. Complementary findings have been made in the monkey prefrontal and posterior parietal cortex; both in the highly trained (10)(11)(12)(13)(14)(15)(16)(17)(18) and in the numerically naïve monkey (30), numerosity is encoded by a labeled-line code. Second, neuronal discharges of selective neurons proved to be relevant for the crows' correct performance; if the neurons did not properly encode their preferred numerosity, the crow was prone to make mistakes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prefrontal region at the apex of the cortical hierarchy processes social signals 35 and thus could be strategically situated to regulate communicative signals. Neurons in the PFC receive highly processed information to represent abstract categories 46,47 irrespective of sensory modality 48 . The PFC actively retrieves associative representations from long-term memory for top-down control 49 and establishes semantic associations between arbitrary items and meaningful categories 50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have shown that neurons in the PFC of numerically naive monkeys tune to a preferred numerosity [48] , independent of sensory modality [49] . These neurons may potentially subserve the neuronal mechanisms underlying WM quantity.…”
Section: Prefrontal Cortex and Wm Quantitymentioning
confidence: 99%